2011
DOI: 10.1111/j.1759-8893.2011.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual/reproductive health and the pharmacist: what is known and what is needed?

Abstract: Recognition of pharmacists' role in sexual and reproductive health is growing. There is a substantial body of literature on pharmacists' participation in this area of health care that has led to significantly improved access for the public. In this paper, the author examines the current practices of pharmacists providing pharmaceutical care in sexual and reproductive health. This leads into a discussion of the public's interest and other healthcare providers' perceptions of the pharmacist role in sexual and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
3
0
2
Order By: Relevance
“…30 Other reviews have also focused on pharmacists' and users' knowledge, attitudes, experiences and perspectives related to contraception as well as a broader spectrum of SRH services. [31][32][33][34][35][36] Overall, the available literature highlights positive users' experiences, implementation is feasible, and also some challenges for pharmacy staff and users. However, these reviews have not addressed the topic from the service organisation, implementation and delivery perspective.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…30 Other reviews have also focused on pharmacists' and users' knowledge, attitudes, experiences and perspectives related to contraception as well as a broader spectrum of SRH services. [31][32][33][34][35][36] Overall, the available literature highlights positive users' experiences, implementation is feasible, and also some challenges for pharmacy staff and users. However, these reviews have not addressed the topic from the service organisation, implementation and delivery perspective.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Although interest in SRH has increased in recent years, there is little research synthesising professional pharmacy services across a broad spectrum of SRH areas. [33][34][35][36] Clarity is needed with respect to pharmacists' roles in SRH as well as the types of professional pharmacy services that may be delivered in community pharmacies to better serve the needs of the community. Addressing this gap in the literature is critical to position pharmacists as SRH providers, especially now that access issues have been exacerbated during the COVID-19 pandemic, and pharmacists are perceived as crucial in emergency response.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Although literature shows increasing enthusiasm for sexual healthcare delivered through community pharmacies (Chin, 2011;Maderas et al, 2008;Eades et al, 2011), a systematic review of the contribution of pharmacists to public health concluded that there was insufficient evidence for their role in sexual health . There has been only one short review of the contribution of community pharmacy to sexual health (Chin, 2011). There have been reviews of the contribution to public health generally Anderson et al, 2009;Anderson et al, 2005), and to the delivery of emergency hormonal contraception specifically (Anderson and Blenkinsopp, 2006).…”
Section: Justification For the Methodologymentioning
confidence: 99%
“…Todos os anos, mais de 120 milhões de casais têm uma necessidade não atendida de contracepção, 80 milhões de mulheres têm gravidez não desejada, sendo que 45 milhões dessas mulheres terminam em aborto. Nesse cenário, mais de meio milhão de mulheres morrem por complicações associadas à gravidez, parto e ao período pós-parto e 340 milhões de pessoas adquirem novas infecções sexualmente transmissíveis, entre outras questões urgentes que certamente precisam de maior atenção dos profissionais de saúde, incluindo farmacêuticos (Chin, 2011).…”
Section: Introductionunclassified
“…Investigações de práticas de dispensação e aconselhamento de farmacêuticos sobre o fornecimento de contraceptivos também estão sendo estudadas ativamente. A capacidade dos farmacêuticos de dispensar e educar o público, especialmente adolescentes, sobre a prevenção de gravidez indesejada e infecção sexualmente transmissível através do uso de métodos contraceptivos tem sido amplamente estudada (Chin, 2011;Leal & Rodrigues, 2019).…”
Section: Introductionunclassified